A Single User Millimeter Wave Massive MIMO System using Defected Ground Structure and Metasurface Antenna Arrays - Mulla, Mustafa; Sohail, Muhammad; Ulusoy, Ali Hakan; Uyguroglu, Rasime; Rizaner, Ahmet; Amca, Hasan (IEEE, 2021)
In this study, we designed a single user millimeter wave massive MIMO system using the defected ground structure and metasurface square patch antenna array in the transmitter and receiver. Since power reduction is a key factor for the 5G technology, hybrid precoding is implemented to enhance the power performance of the millimeter-wave large-scale antenna systems with a minimum spectral efficiency loss compared with the fully digital baseband precoders. Hence, Barzilai-Borwein (BB) based alternating minimization algorithm is applied to compute the hybrid precoders and simulation results are illustrated for different setups to compare the proposed system with the competing methods in the literature. Simulation results are supported by additional performance parameters and demonstrate that the BB algorithm would be a strong candidate for hybrid precoding. The transmitting and receiving antenna arrays are designed using novel defected ground structure and metasurface patch antenna to achieve antenna miniaturization and reduced mutual coupling in array elements. The proposed single element antenna with a compact size operates at 28 GHz with a bandwidth of 3.1 GHz and gain of about 6.28 dB. Antenna arrays are optimized iteratively to achieve high isolation between antennas to avoid the degradation in antenna radiation properties.
29th IEEE Conference on Signal Processing and Communications Applications (SIU) -- JUN 09-11, 2021 -- ELECTR NETWORK
Keywords: 5G; millimeter wave; massive MIMO; hybrid precoding; microstrip patch antenna; defected ground structure; metasurface